2004
DOI: 10.1099/mic.0.26791-0
|View full text |Cite
|
Sign up to set email alerts
|

Flagella and curli fimbriae are important for the growth of Salmonella enterica serovars in hen eggs

Abstract: Salmonella enterica serovar Enteritidis is unable to multiply in the albumen of fresh eggs and must gain access to the yolk contents in order to multiply to a high level (>10 6 c.f.u. per ml egg contents). As human Salmonella infections resulting from the consumption of infected eggs more frequently involve serovar Enteritidis phage type (PT) 4 than other serovars or PTs, a number of isolates of various S. enterica serovars were examined for their ability to multiply to a high level in eggs over a period of 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 39 publications
2
56
1
1
Order By: Relevance
“…A positive regulator of Type I fimbriae expression was also induced in the reproductive tract and in laid eggs (Gantois et al 2008b). A role for curli fimbriae and flagella in growth in eggs has also been reported (Cogan et al 2004), but the role of other surface structures, including T3SSs, in reproductive tract colonization requires further study. Recent studies have indicated that the SPI-2 regulator SsrA is required for colonization of the reproductive tract after intravenous inoculation of chickens (Bohez et al 2008), however potential for pleiotropic effects exists and the role of SPI-2 genes per se has not been reported.…”
Section: Molecular Basis Of Colonization Of the Avian Reproductive Trmentioning
confidence: 99%
“…A positive regulator of Type I fimbriae expression was also induced in the reproductive tract and in laid eggs (Gantois et al 2008b). A role for curli fimbriae and flagella in growth in eggs has also been reported (Cogan et al 2004), but the role of other surface structures, including T3SSs, in reproductive tract colonization requires further study. Recent studies have indicated that the SPI-2 regulator SsrA is required for colonization of the reproductive tract after intravenous inoculation of chickens (Bohez et al 2008), however potential for pleiotropic effects exists and the role of SPI-2 genes per se has not been reported.…”
Section: Molecular Basis Of Colonization Of the Avian Reproductive Trmentioning
confidence: 99%
“…However, there is conflicting evidence for the contribution of flagella to virulence in S. Enteritidis. Flagellar mutants have been shown to be less proficient in colonizing eggs than wild-type S. Enteritidis (Cogan, et al, 2004). In 20-day-old chickens, Parker et al (Parker & Guard-Petter, 2001) observed that disruption of flagella (by deletion of transcriptional regulator FlhD) caused enhanced invasiveness upon oral challenge.…”
Section: Flagellamentioning
confidence: 99%
“…Quantitative estimation of the impact of setting a new target for the reduction of Salmonella in breeding hens of Gallus gallus numbers) include high molecular mass lipopolysaccharide and surface appendages such as curli, type I fimbriae and flagella (Cogan et al, 2004;De Buck et al, 2004;Guard-Bouldin et al, 2004;Guard-Petter, 2001). …”
Section: Smentioning
confidence: 99%